RECOD @ placing task of MediaEval 2015 - Li, Lin Tzy; Muñoz, Javier A. V.; Almeida, Jurandy; Calumby, Rodrigo T.; Penatti, Otávio A. B.; Dourado, Ícaro C.; Nogueira, Keiller; Mendes, Pedro R.; Pereira, Luís A. M.; Pedronette, Daniel C. G. [UNESP]; Dos Santos, Jefersson A.; Gonçalves, Marcos A.; et al. (My University, 2015)
In this work, we describe the approach proposed by the RECOD team for the Placing Task, Locale-based sub-task, at MediaEval 2015. Our approach is based on the use of as much evidence as possible (textual, visual, and/or audio descriptors) to automatically assign geographical locations to images and videos.
Keywords: Descriptors; Geographical locations; Subtasks